Utility of population pharmacokinetic modeling in the assessment of therapeutic protein‐drug interactions. (6th December 2013) - Chow, Andrew T.; Earp, Justin C.; Gupta, Manish; Hanley, William; Hu, Chuanpu; Wang, Diane D.; Zajic, Stefan; Zhu, Min
Abstract Assessment of pharmacokinetic (PK) based drug–drug interactions (DDI) is essential for ensuring patient safety and drug efficacy. With the substantial increase in therapeutic proteins (TP) entering the market and drug development, evaluation of TP‐drug interaction (TPDI) has become increasingly important. Unlike for small molecule (e.g., chemical‐based) drugs, conducting TPDI studies often presents logistical challenges, while the population PK (PPK) modeling may be a viable approach dealing with the issues. A working group was formed with members from the pharmaceutical industry and the FDA to assess the utility of PPK‐based TPDI assessment including study designs, data analysis methods, and implementation strategy. This paper summarizes key issues for consideration as well as a proposed strategy with focuses on (1) PPK approach for exploratory assessment; (2) PPK approach for confirmatory assessment; (3) importance of data quality; (4) implementation strategy; and (5) potential regulatory implications. Advantages and limitations of the approach are also discussed.